Study of Fluidic Ejection and Nanodroplet Formation - Nguyen, Van Quang; Nguyen Xuan, Chung; Hoang Tien, Dung; Nguyen Nhu, Tung; Pham Tien, Hung; Nguyen Tien, Tung; Nguyen Chi, Tam (Applications of Modelling and Simulation, 2021)
Study of fluidic molecule ejection through nozzle diameters of 27.5, 30 and 40 Angstrom (Å) at temperatures of 310, 315 and 333 Kelvin (K) is performed by using the molecular dynamics simulation method. The results show that almost all molecules were ejected out through the nozzle and formed up the fluidic jets on the nozzle’s surfaces for all above cases. However, a fluidic jet was not separated out from the nozzle’s surface for the case of the 310 K temperature and 27.5 Å diameter under any the pushing force values and ejection time. Otherwise, the jets separate out from the nozzle’s surface to produce the fluidic nanodroplets when increasing either the nozzle diameter to 30 Å or the temperature magnitude to 315 K. These demonstrate the nozzle size and temperature magnitude decide to the fluidic ejection and nanodroplet formation.